LABORATORY STUDY ON THE OPTIMIZATION OF IPLT SUMUR BATU DEWATERING UNIT USING DIFFERENT COAGULANTS - Sandra Madonna; Sirin Fairus; Nadya Nurul Amelinda (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2019)
Aim: The aim of this study is to determine the most effective type and concentration of coagulant to reduce TDS, TSS, BOD and COD Sumur Batu Fecal Treatment Plant or Instalasi Pengolahan Lumpur Tinja (IPLT) Sumur Batu. Methodology and Results: Using the jar test method at a laboratory scale, the types of coagulants of PAC, Alum and FeSO4 with varied concentration of 70 mg/L, 137.5 mg/L and 200 mg/L were used. Additionally, Polyacrylamide was also used in the study with concentration varied between 0.1 mg/L, 0.6 mg/L, and 1.1 mg/L adjusted to the concentration in the field. Conclusion, significance and impact study: Results showed that Alum with a concentration of  200 mg/L was the most effective coagulant, with removal efficiency for each parameter is as follows TDS = 82.17%, TSS = 67.69%, BOD = 60.16%, and COD = 59.76%.